{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

10-mmch-04_0

# 10-mmch-04_0 - 04" I 20106 10 9 2 16 2007...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 04 (") I - 20106 : 10 - 9 : 2 : 16 : 2007 : 15.6.2007 : " www.openu.ac.il/sheilta . , 1 - : , 2 - , - . - 1 . f ( x) = x 2 - 1 . S ( P) = s( P) - [0,1] P . [0,1] - f . . 2 :- [0,1] f x f ( x) = 0 x [ 1 , 3 ] 4 4 9 1 - S ( P ) = 8 16 . [0,1] P = {0, 1 , 1 , 3 ,1} , s ( P ) = 8 2 4 .1 .2 . [0,1] - f 25 3 . f ( x) = 3 . s ( P ) > 0 [0,6] P . f ( x) dx = 2 0 5 x .1 .2 4 4x3 . f ( x) = x 2 + 2 0 x 1 :- [0,2] f 1< x 2 . [0,2] - f : c 2 - c1 x4 + c 1 F ( x) = x3 3 + 2 x + c2 0 x1 1< x 2 .1 .2 . [0,2] - f - 5 . [-1,3] - f ( x) = x - x2 2 .1 .2 . [-1,3] - f ( x) = x - 26 6 sin x . [-2, 2] f ( x) = 1 sin x 1 1 x sin x . [0,1] g ( x) = 3 x0 x>0 .1 x0 x=0 .2 7 . [a , b] - f . S ( P) = f ( x) dx - [a , b] P a b .1 . [a , b] - f , S ( P) = f ( x) dx - [a , b] P a b .2 8 ,( ) f ( x)dx = 0 - [0 ,1] - 0 1 f .1 . [0 , 1] - f ,( ) f ( x)dx = 0 - [0 ,1] - 0 1 f .2 . [0 , 1] - f 9 . [a , b] - f . [a , b] - f , f ( x)dx = (b - a ) sup f ([a, b]) a b .1 . [a , b] - f , [a , b] - f - 27 f ( x)dx = (b - a) sup f ([a, b]) a b .2 10 [a , b] h - g , f . x f ( x) g ( x) h( x) , f ( x)dx = h( x)dx - [a , b] - h - f a a b b .1 . [a , b] - g . [a , b] - f , (a, b) - , [a , b] - f .2 11 . f ( x)dx = f (c)(b - a ) - (a, b) - c , [a , b] - f a b .1 . [a , b] - x f ( x) = 0 , f 2 ( x)dx = 0 - [a , b] - f a b .2 12 , [a , b] - x f (t ) dt = 0 [a , b] - a b x f .1 . [a , b] - x f ( x) = 0 , f (t )dt = g (t )dt [a , b] - g - f a a b .2 . f ( x) = g ( x) [a , b] - x 13 F ( x) = f (t )dt , R - f 0 x .( R - F - ) . R - F , R - f . R - F , R - f .1 .2 28 14 :- [0 , 1] f 1 . f ( x) = 0 x= 1 - n n . S ( P) < [0 , 1] P > 0 . f ( x) dx = 0 [0 , 1] f 0 1 .1 .2 15 . M - m , [a , b] g - f . m g ( x) dx f ( x) g ( x) dx M g ( x) dx x m f ( x) M a a a b b b .1 1 2 9 - x2 dx 16 0 1 5- x 9 .2 16 . 5 - g ( x) = x - f ( x) = x 3 12 .1 .2 h( x) = sin x - cos x . 2 x - x = 2 - x = - 2 29 30 ...
View Full Document

{[ snackBarMessage ]}